Derivation of Global Parametric Performance of Mixed Flow Hydraulic Turbine Using CFD - Khare, Ruchi; Prasad, Vishnu Prasad; Kumar, Sushil (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
The testing of physical turbine models is costly, time consuming and subject to limitations of laboratory setup to meet International Electro technical Commission (IEC) standards. Computational fluid dynamics (CFD) has emerged as a powerful tool for funding numerical solutions of wide range of flow equations whose analytical solutions are not feasible. CFD also minimizes the requirement of model testing. The present work deals with simulation of 3D flow in mixed flow (Francis) turbine passage; i.e., stay vane, guide vane, runner and draft tube using ANSYS CFX 10 software for study of flow pattern within turbine space and computation of various losses and efficiency at different operating regimes. The computed values and variation of performance parameters are found to bear close comparison with experimental results. Key words: Hydraulic turbine; Performance; Computational fluid dynamics; Efficiency; Losses DOI: 10.3126/hn.v7i0.4239 Hydro Nepal Journal of Water, Energy and Environment Vol. 7, July, 2010 Page: 60-64 Uploaded date: 31 January, 2011